1970
DOI: 10.1126/science.167.3926.1743
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of Habituation and Dishabituation of the Gill-Withdrawal Reflex in Aplysia

Abstract: We have examinived the nieural correlates of habittuatiotn atid dishabitiuation of tlhe gill-withdrwal reflex in Aplysia. We obtained intracelllular recordings from identified gill motor neurons in the abdominal ganglionz of a semi-intact preparation of Aplysia wlhile we simultaneously recorded behavior responises of the gill. Habituation and dishabituation were not due to peripheral changes in either the sensory receptors or the gill musculature butt were caused by changes in the amplitlude of the excitatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
0
1

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(84 citation statements)
references
References 3 publications
7
76
0
1
Order By: Relevance
“…The possible role and site of homosynaptic depression during habituation in Aplysia was investigated initially in the siphonelicited gill withdrawal reflex Kupfermann et al, 1970;Pinsker et al, 1970;Carew et al, 1971). This work supported the conclusion that homosynaptic depression at the LE siphon sensory neurons underlies the response decrement observed in the behaving animal.…”
Section: Habituation In the Gill Withdrawal Reflexsupporting
confidence: 64%
“…The possible role and site of homosynaptic depression during habituation in Aplysia was investigated initially in the siphonelicited gill withdrawal reflex Kupfermann et al, 1970;Pinsker et al, 1970;Carew et al, 1971). This work supported the conclusion that homosynaptic depression at the LE siphon sensory neurons underlies the response decrement observed in the behaving animal.…”
Section: Habituation In the Gill Withdrawal Reflexsupporting
confidence: 64%
“…Studies of the cellular correlates of habituation have shown that tactile stimulation of the siphon skin initiates a complex excitatory postsynaptic potential (EPSP), produced largely by direct synaptic connections from the sensory cells (7,13), that discharges the motor cells and causes gill contraction. Habituation produces a progressive decrease in the complex EPSP (17). Analyses of the various components of the reflex during short-term habituation (including measurements of the threshold and input conductance of the motor cell) indicate that the critical change occurs at the synapses between the sensory cell and the motor neurons and interneurons (refs.…”
Section: Methodsmentioning
confidence: 99%
“…The gill-withdrawal reflex studied in Aplysia is a classic example of the habituation (desensitization) of reflex in response to repeated non-noxious stimuli [6][7][8]. Intuitively, this adaptation corresponds to the interpretation that since the sea slug is constantly bombarded with stimuli from sea waves, those harmless stimuli can be ignored if they do not represent potential threats to the animal.…”
Section: Gill-withdrawal Reflex As An Examplementioning
confidence: 99%